Hydrogen Promotes the M1 Macrophage Conversion During the Polarization of Macrophages in Necrotizing Enterocolitis - Yu, Shenghua; Lv, ZhiBao; Gao, Zhimei; Shi, Jingyi; Sheng, Qingfeng; Zheng, Lulu; Zhou, Junmei; Wang, Xueli (Frontiers in Pediatrics, 2021)
Background: Hydrogen is protective against intestinal injury in necrotizing enterocolitis (NEC), mainly through to alleviate inflammation response. The M1 macrophages can promote inflammation. We hypothesized that hydrogen would promote the M1 macrophages conversion during the polarization and reduce the inflammatory factors in NEC. Methods: We used M1 and M2 macrophages induced from RAW264.7 cells and bone marrow-derived macrophages, models of NEC and macrophages derived from spleens, abdominal lymph nodes and lamina propria in model mice. Cytokines, CD16/32 and CD206 were measured by quantitative PCR, flow cytometry. Nuclear factor-κB (NF-κB) p65 were determined by western blot. Histology staining were used to assess the severity of NEC. Results: Macrophages were successfully polarized to M1 or M2 by assessing the expression of inflammatory factors. Pro-inflammatory factors and CD16/32 in M1 macrophages were decreased, and the expression of CD16/32 in lamina propria were inhibited after treatment with hydrogen, but the changes has no effects in other tissues. Hydrogen inhibited the NF-κB p65 in M1 macrophages nucleus and distal ileum of NEC. HE staining showed hydrogen could attenuate the severity of NEC. Conclusion: Hydrogen could attenuate the severity of NEC through promoting M1 macrophages conversion by inhibited the expression of NF-κB p65 in the nucleus.